2018
DOI: 10.1016/j.algal.2018.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microalgal biomasses as functional food ingredients: Focus on the composition of cell wall related polysaccharides

Abstract: Microalgae are rich in several nutritional and health-beneficial components, showing great potential as functional food ingredients. To this extent, knowledge of the biomass composition is essential in the selection of suitable microalgae species for specific food applications. Surprisingly, although cell wall polysaccharides are generally reported to play a role in functionality, limited attention has been given to the cell wall related polysaccharides of microalgae so far. Therefore, this study aimed to char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
117
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(134 citation statements)
references
References 104 publications
(121 reference statements)
14
117
2
1
Order By: Relevance
“…This is likely due to the N. oculata cell walls being destroyed or denatured under the HTHP conditions. It is currently unknown why the C. vulgaris cells did not also become digestible under the same conditions, but this is likely related to differences in the structure and composition of the cell walls between the two species (Bernaerts et al, 2018). Because N. oculata contains large amounts of EPA, which is an essential fatty acid for the larvae of many marine species (Brown et al, 1997;Watanabe et al, 1983), HTHP-treated N. oculata have high potential for the nutritional enrichment of Artemia before they are fed to larvae and for the supplementation of larval rearing water during the period of Artemia feeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely due to the N. oculata cell walls being destroyed or denatured under the HTHP conditions. It is currently unknown why the C. vulgaris cells did not also become digestible under the same conditions, but this is likely related to differences in the structure and composition of the cell walls between the two species (Bernaerts et al, 2018). Because N. oculata contains large amounts of EPA, which is an essential fatty acid for the larvae of many marine species (Brown et al, 1997;Watanabe et al, 1983), HTHP-treated N. oculata have high potential for the nutritional enrichment of Artemia before they are fed to larvae and for the supplementation of larval rearing water during the period of Artemia feeding.…”
Section: Discussionmentioning
confidence: 99%
“…which are able to feed; Sorgeloos et al, 2001). It is currently unknown why the C. vulgaris cells did not also become digestible under the same conditions, but this is likely related to differences in the structure and composition of the cell walls between the two species (Bernaerts et al, 2018). This is likely due to the N. oculata cell walls being destroyed or denatured under the HTHP conditions.…”
Section: Effect Of Hthp Treatment On the Total Lipid Content And Famentioning
confidence: 99%
“…Microalgae biomass is ownerless in lignocellulosic material and full of lipids and protein, so it is considered as an important alternative feedstock for biofuels [10]. The differences in cell size, shape and structure of algae species, and the characteristics of the wastewater media can effect on the lipid recovery efficiency [11,12]. Bernaerts et al [12]demonstrated that algal biomass components can be altered by modifying the cultivation conditions, such as nutrients concentration and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The differences in cell size, shape and structure of algae species, and the characteristics of the wastewater media can effect on the lipid recovery efficiency [11,12]. Bernaerts et al [12]demonstrated that algal biomass components can be altered by modifying the cultivation conditions, such as nutrients concentration and temperature. Patrícya et al demonstrated that maximum total lipid of mixed algae cultures cultivated in a stabilization pond system treating sewage was 33.7±5.3% [7].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, in the field of biodegradable materials, there are many cases of introducing biological components into resin matrix to give us some inspiration. From previous studies that produced bioplastics from starch, protein or inorganic filer [10][11][12][13][14], considering that algae from Lake Chao are rich in phyco-protein and polysaccharide [15][16][17][18][19], if the properties of the biomacromolecules can be changed through physical or chemical means, the biomacromolecules can be used to prepare plastic products [20][21][22][23][24][25]. For example, edible biofilms or packaging materials were prepared using starch and protein as raw materials or by using the properties of hydroxyl groups in protein macromolecules grafted with compatibilizers [26,27], such as maleic anhydride, by introducing biomacromolecules into the low-density polyethylene (LDPE) chain [28,29].…”
Section: Introductionmentioning
confidence: 99%